Pengetahuan Menggosok Gigi dan Karies Gigi : Studi Kasus di SDN Batulaccu - Usman, Faradillah; Pariati; Aulyah, Dwi Rezky; Nurhaedah; Sartika, Dewi (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2024)
Dental and oral health is part of the health of a person's body. Dental and oral health is a state of being free from oral disease and throat cancer, infections and sores of the mouth, gum disease and periodontal tissue, disorders that limit an individual's capacity in chewing, smiling, speaking and psycho-social well-being. Knowledge is very closely related to education, where it is expected that with higher education, the person will be more knowledge-widespread. Dental health efforts need to be reviewed from environmental aspects, knowledge, education, public awareness and dental health handling including prevention and treatment. Government efforts in building health certainly require people who can provide explanations about dental health and existing rules in the health sector, especially dental and oral health. One of the dental and oral health diseases is cavities. This disease is an infection that damages the structure of the hard tissue of the tooth caused by several acidic bacteria that can damage due to carbohydrate fermentation reactions. Dental caries is a disease that is very susceptible to occur in children and its prevalence continues to increase. This study aims to determine the picture of brushing knowledge on the status of dental caries in grade 3 and 4 students at SD Negeri Batulaccu Makassar, the research method used is descriptive research with a cross-sectional research design. The samples studied using purposive sampling were 36 people. The results showed that knowledge of brushing teeth was still lacking with moderate criteria of 61.2%, caries status in 14 students with very high criteria of 39%, and knowledge of brushing teeth with medium criteria as many as 8 respondents with criteria of DMF-/def-t caries of 22.3%.